2017
DOI: 10.1177/0886260517730027
|View full text |Cite
|
Sign up to set email alerts
|

Intervening in a “Sketchy Situation”: Exploring the Moral Motivations of College Bystanders of Sexual Assault

Abstract: This mixed-methods research explored the moral motivations of undergraduates who identified as bystanders in a situation of potential sexual assault. In the quantitative analysis, we examined the difference between interveners and noninterveners with regard to their scores on the Moral Foundations Questionnaire-30 Item (MFQ-30), which considers five moral foundations from Moral Foundations Theory (MFT) of care/harm, fairness/cheating, loyalty/betrayal, authority/subversion, and sanctity/degradation, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Broadly, sex buying research should include measures of morality, particularly purity moralization, to avoid omitted variable bias. In addition, as was noted previously, research documents a link between purity moralization and key variables in existing explanations for sex buying, such as sexist ideology and attitudes about rape and sexual assault (Barnett & Hilz, 2018;Gable et al, 2017;Vecina & Piñuela, 2017). Interestingly, however, our findings suggest a more complicated relationship among these concepts than prior sex buying research has explored so far, insofar as purity moralization may be associated with greater acceptance of sexual violence (Barnett & Hilz, 2018;Gable et al, 2017) but reduced involvement in sex buying, which has been described by some scholars as a form of sexual violence in itself (Farley et al, 2017).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Broadly, sex buying research should include measures of morality, particularly purity moralization, to avoid omitted variable bias. In addition, as was noted previously, research documents a link between purity moralization and key variables in existing explanations for sex buying, such as sexist ideology and attitudes about rape and sexual assault (Barnett & Hilz, 2018;Gable et al, 2017;Vecina & Piñuela, 2017). Interestingly, however, our findings suggest a more complicated relationship among these concepts than prior sex buying research has explored so far, insofar as purity moralization may be associated with greater acceptance of sexual violence (Barnett & Hilz, 2018;Gable et al, 2017) but reduced involvement in sex buying, which has been described by some scholars as a form of sexual violence in itself (Farley et al, 2017).…”
Section: Discussionmentioning
confidence: 61%
“…First, insofar as morality is a potentially powerful constraint on sex buying, the theoretical models described in prior sex buying research may be incomplete. Second, research documents that moral beliefs differ across social and demographic groups (Graham et al, 2009(Graham et al, , 2011Miles, 2014), and are associated with attitudes regarding sexual permissiveness (Haidt & Hersh, 2001), rape myth acceptance (Barnett & Hilz, 2018;Gable et al, 2017), sexism (Vecina & Piñuela, 2017), and adherence to traditional gender roles (Graham et al, 2011). Thus, empirically, prior research focusing solely on demographic or genderbased explanations for sex buying may suffer from omitted variable bias and either overstate or understate the relationships between sex buying and other theoretically relevant variables.…”
Section: Why Men Buy Sexmentioning
confidence: 99%
“…A meta-analysis of pornography consumption has been found to be correlated positively and highly with actual acts of sexual aggression, acceptance of rape myths, the proclivity to sexual harass and also interpersonal violence These inclinations are obviously and directly linked to a state of one's weak ability to have empathy and care for others thus it is logical to have lower scores in the Harm/Care foundation (Dawson et al, 2021). On the other hand, interestingly, people who were to score high in the rape myth acceptance, scored higher in the Loyalty/Betrayal foundation as a study done to explore the moral foundations of interveners and non-interveners when encountered with a sexual assault (Gable et al, 2021). Therefore, a hypothesis can be posited that one's pornography consumption affects indirectly one's loyalty/betrayal foundation due to direct effect of pornography consumption towards one's acceptance of rape myths.…”
Section: The Association Between Pornography Addiction and Moral Judg...mentioning
confidence: 99%
“…Other research has found that students often describe their intervention opportunities as those primarily involving with friends, whereby prosocial helping is on behalf of their friend, the potential victim, or a potential perpetrator, as opposed to a stranger in either role, who is known to them, and tactics typically take on an indirect strategy, that is, distancing the victim from the perpetrator (Moschella et al, 2018) or distracting the perpetrator (Gable et al, 2017). A more recent qualitative study replicated these findings, yet the authors importantly critiqued such reliance on indirect, nonconfrontational intervention strategies as missed opportunities to combat sexism norms and problematic behavior among potential perpetrators (Reid & Dundes, 2017).…”
Section: Types Of Bystander Intervention Responsesmentioning
confidence: 99%
“…Whereas most quantitative designs in the bystander intervention research explicitly describe risk situations to assess students’ bystander behavior when witnessing them (e.g., based on Banyard et al’s [2004] Bystander Behavior Scale) or ask participants whether they have performed specific intervention actions, qualitative designs can allow students to discuss their intervention behavior in the context of what situations have been viewed as risky for them and how the situation unfolded. In this approach, researchers can gain insight into how students conceptualize situations at risk for sexual violence, a critical component for understanding the barriers at this step in the model (Burn, 2009; Gable, Lamb, Brodt, & Atwell, 2017; Latané & Darley, 1970), as well as understand what motivated them to take intervention responsibility and the actions they took to intervene. In a qualitative investigation of students’ intervention actions, one study used a dramatize skit where a male student took a drunk, female student to his room; students reported a variety of strategies that could be used to disrupt the situation (McMahon, Hoffman, McMahon, Zucker, & Koenick, 2013).…”
Section: Types Of Bystander Intervention Responsesmentioning
confidence: 99%